Implementation Strategies for Quality Improvement in Palliative Care: A Scoping Review - Yunyun Dai; Barbara A. Daveson; Luyu Gan; Jinfeng Ding; Yongyi Chen; Claire E. Johnson (Wiley, 2024)
ABSTRACT Background Quality improvement (QI) programs based on person‐centred outcome measures (PCOMs) play an important role in promoting optimal palliative care. However, routine use of PCOMs has been slow and difficult to implement, including within QI programs. Objective This study aimed to identify implementation strategies that support the implementation of PCOMs as routine practice in hospital‐based palliative care, as well as the implementation theories, models and frameworks (TMFs) guiding the design of these implementation strategies. Methods A scoping review was conducted in accordance with the Joanna Briggs Institute (JBI) Scoping Review framework. Four databases (Medline, CINAHL, Scopus and PubMed) were systematically searched for literature published between 1 January 1990 and 8 March 2024. Results One hundred and fifteen unique implementation strategies, identified from 11 included studies, were mapped onto the 73 Expert Recommendations for Implementing Change (ERIC) discrete implementation strategies, covering 52% of the ERIC strategies. The most commonly used categories were train and educate stakeholders, and support clinicians, followed by develop stakeholder interrelationships and use evaluation and iterative strategies. Three key themes emerged: what to do; how to do it; and who to do it with. Only four studies employed TMFs to guide the design of the implementation strategies in this review. Conclusions To promote the implementation of PCOM‐based QI programs, strategies should be developed based on identified/potential barriers and facilitators by using rigorous TMFs. The components of the implementation strategies must be reported transparently and consistently to enable replication and measurement in future research and practice. Patient and Public Contribution This scoping review does not directly involve patients or the general public in its design or execution. However, it is part of an implementation study aimed at integrating the Palliative Care Outcome Collaboration (PCOC) model into routine clinical practice at a cancer hospital in China. Before the formal implementation, palliative care professionals from this hospital highlighted the need for a comprehensive analysis of existing evidence to support the effective adoption of the PCOC model in their specific clinical setting.